Development and validation of a tool to measure telehealth educational environment (THEEM) - Marium Arif; Madiha Sajjad; Rehan Ahmed Khan; Hafiz Rabbi ul Ehsan (BMC Medical Education)
Abstract Background Telehealth is gaining importance in improving healthcare access and outcomes, particularly in underserved regions. Despite its potential, healthcare providers in developing countries struggle to effectively utilize telehealth tools, highlighting the need for structured training. This study aims to develop and validate a specialized tool to assess the telehealth educational environment, addressing the unique challenges of integrating clinical, technological, and interpersonal skills in telehealth education. Objectives (1) To develop a tool for measuring the telehealth educational environment, addressing the unique aspects of telehealth education. (2) To evaluate the validity and reliability of the tool. Method This mixed-methods exploratory study had two phases. In Phase 1, the THEEM tool was developed through a literature review and expert feedback. In Phase 2, the tool was validated using content validity, response process validity via cognitive interviews, and construct validity through Exploratory factor analysis (EFA). Reliability was assessed using Cronbach’s alpha. Participants included telehealth physicians, selected via purposive sampling. Data analysis involved calculating the content validity index for items (CVI-I) and the scale (CVI-S), with values ≥ 0.7. For factor analysis, eigenvalues > 1 and factor loadings ≥ 0.50 were retained. Cronbach’s alpha for internal consistency was considered acceptable at ≥ 0.7. Results The Preliminary THEEM tool consisted of 35 items. Following content validity through expert validation, the number of items was reduced to 32 based on I-CVI values. S-CVI was 0.86. Exploratory factor analysis yielded three factors with a further reduction in the item number to 30. Internal consistency of the final tool with 30 items was calculated as 0·9, suggesting excellent internal consistency of the tool. Conclusion The THEEM tool provides a valuable, reliable, and valid instrument for assessing the telehealth educational environment. Its development fills a significant gap in existing measurement tools, specifically addressing the needs of telehealth education.